Enhancing cognitive and collaborative outcomes in Islamic education: A classroom action research on the STAD method in aqidah akhlak learning - Saidah, Elbina Mamla; Wahyuni, Wahyuni (STAI Auliaurrasyidin Tembilahan, 2026)
This study examines the effectiveness of the Student Teams Achievement Divisions (STAD) cooperative learning method in improving students’ learning outcomes in the